Case report: The efficacy of adding high doses of intravenous vitamin C to the combination therapy of atezolizumab and bevacizumab in unresectable HCC - Kian, Waleed; Remilah, Areen A.; Shatat, Celine; Spector, Maria; Roisman, Laila C.; Ryvo, Larisa (Frontiers in Medicine, 2024)
Introduction: Vitamin C (L-ascorbic acid) plays a vital role in human physiology, serving as both an antioxidant and a cofactor in enzymatic reactions. High-dose intravenous Vitamin C can achieve significantly elevated plasma concentrations, potentially enhancing its anticancer effects. This case study explores the synergistic impact of high-dose intravenous Vitamin C in combination with Bevacizumab and Atezolizumab in the treatment of a patient with unresectable hepatocellular carcinoma (HCC). Case Presentation: A 68-year-old male was diagnosed with unresectable HCC, presenting with elevated liver enzymes and an alpha-fetoprotein (AFP) level of 2018 ng/mL. Initial treatment with Atezolizumab and Bevacizumab commenced in February 2022. Although imaging indicated stable disease, AFP levels decreased modestly to 1526 ng/mL, while liver function tests remained elevated, accompanied by further clinical deterioration and weight loss. Subsequently, intravenous Vitamin C (30 grams) was introduced into the treatment regimen. This addition led to a rapid and significant reduction in AFP levels, normalization of liver function tests, and marked improvement in clinical symptoms. The patient continued on this combined regimen of Vitamin C, Atezolizumab, and Bevacizumab. Four months later, CT scans revealed significant tumor shrinkage and necrosis. As of thirty months post-diagnosis, the patient remains on the regimen with normal liver function and an AFP level of 1.8 ng/mL, maintaining normal activities and stable weight. Conclusion: To our knowledge, this is the first reported case of combining high-dose intravenous vitamin C with Bevacizumab and Atezolizumab, which proved to be safe and resulted in significant clinical and radiological improvements in unresectable hepatocellular carcinoma (HCC). Further studies are recommended to explore the potential of this combination therapy.